Logic Model Basics - Glenn D. Israel (EDIS)
WC106, a 5-page illustrated fact sheet by Glenn D. Israel, explains what logic models are and provides steps for creating a basic logic model. Includes references. Published by the UF Department of Agricultural Education and Communication, October 2010.